Labor market reforms in Europe : towards more flexicure labor markets? - Eichhorst, Werner [Verfasser]; Marx, Paul [Verfasser]; Wehner, Caroline [Verfasser] (My University, 2017)
"Labor market segmentation refers to a salient divide between secure and insecure jobs and is related to problems in important areas, including macro-economic efficiency, workers' well-being and repercussions for social cohesion. EU-28 countries have started a new wave of labor market reforms in the aftermath of the 2008/2009 crisis to tackle a number of issues, including labor market segmentation. This particularly concerns reforms in: (1) employment protection, i.e. dismissal protection and restrictions on fixed-term contracts; (2) unemployment benefit generosity and coverage; and (3) the intensity of active labor market policies. The paper provides an overview of reform patterns and tries to assess whether and to what extent these reforms have led to less dualized, more 'flexicure' labor markets in terms of dismissal protection, the provision of unemployment benefits and access to ALMPs. In particular, we will provide some evidence on potential changes in hirings on temporary contracts." (Authors' abstract, BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 1.2.2.2 Soziale Sicherungssysteme; G 1.2.2.4 Arbeitslosigkeit; I 2.2 Europa; Arbeitsmarkt; Reform; Arbeitsmarktsegmentation; Kündigungsschutz; Arbeitslosenversicherung; Arbeitsmarktpolitik; Berufliche Weiterbildung; Arbeitsloser; Langzeitarbeitsloser; Europa